Application of the Ultrasonic Ring Array Used in UTT for the Reflection Method Examinations of Structures - STASZEWSKI, Wiktor; GUDRA, Tadeusz; OPIELINSKI, Krzysztof J. (Archives of Acoustics, 2021)
The ultrasonic ring array, designed for examining the female breast with the use of ultrasonic transmission tomography (UTT), has been adapted for reflection method trials. By altering the activation time of ultrasonic elementary transducers, the parameters of the focus were changed with the aim at improving the quality of the obtained ultrasound image. For this purpose, a phantom consisting of rods having varying thicknesses was analyzed when moving the position of the focus with the use of dynamic focusing along the symmetry axis of the ring array ranging from 30 to 130 mm from central transducers. In previous trials, which applied an algorithm using the sum of all the acoustic fields, a series of simulations was performed in conditions identical to the phantom trial. This paper documents attempts at improving the parameters of the acoustic field distribution during unconventional focusing. The research here presented is a continuation of examinations focusing on the acoustic field distribution inside the ultrasonic ring array with the aim at finding the best possible cross-section of the female breast using the reflection method.